Challenges experienced by primary caregivers in managing temper tantrums of infants and toddlers in Harare East daycare centres - Muzembe, Hannah Perpetua; Manzunzu, Nomatter (Journal of Innovation and Research in Primary Education, 2025)
This study focuses on the challenges experienced by caregivers in managing temper tantrums. The study was motivated by the constant quest for Early Childhood Development in Zimbabwe which is facing a plethora temper tantrum managing challenges. It is against this backdrop that this study x-rayed the caregivers’ understanding and challenges faced thereof in managing temper tantrums in day care centres in Epworth, Mabvuku and Tafara (EPMAFARA) district in Harare Province. The study was guided by the constructivist paradigm backed up by the Bio-Ecological theory under the qualitative approach to research. A case study design was used, drawing on five day care centres which were purposively sampled, to provide rich data. Caregivers’ experiences were tracked via in-depth interviews, class observations and document analysis. Results of the study indicated caregivers’ partial understanding of infant and toddler temper tantrums. The commonest temper tantrums were, crying, throwing objects around, rolling on the floor and screaming among others. Results showed mixed operational challenges coupled with speculative intervention strategies to curb tantrums. Findings also revealed that teachers who participated in the study were not all professionally trained and could not effectively incorporate theories of child development into their pedagogical practices. Further findings revealed that day care centres were running without government policy on early childhood education for infants and toddlers. It is recommended to policy makers to come up with a policy which clearly articulates the education ideology for infants and toddlers in the country.